Gisela Swetlana Ortriwano and the University of São Paulo: affective relations towards education, research and outreach - Galvão Júnior, Lourival da Cruz (Comunicação & Educação, 2023)
This study analyzes the trajectory and contributions of Gisela Swetlana Ortriwano to the Department of Journalism and Publishing at the School of Communications and Arts, University of São Paulo. Supported by documentary and bibliographic research aligned with the fundamentals of oral history, this work investigates the academic trajectory of the professor and researcher who became a reference for radio and radio journalism studies in Brazil. Based on the testimonies of her colleagues, the text reveals a relationship marked by affection towards a higher education institution where, for more than three decades, Gisela Swetlana Ortriwano worked as a student, professor and researcher.